Trends and periodicities in the annual amount of dry days over Argentina, looking towards the climatic change - Penalba O.; Rivera J.; Bettolli M.L. (Economics of drought and drought preparedness in a climate change context, 2010)
During the second half of the twentieth century, Southeastern South America experienced a positive trend in annual precipitation. Since Argentina is a country whose economy mostly relies on rain-fed agriculture, this trend has favoured the extension of the agricultural frontier, increasing the availability of productive lands. However, this precipitation increase was accompanied by greater interannual variability in precipitation, which increases the risk of droughts and their consequent negative impacts. In this work we analyze the temporal variability of the annual amounts of dry days (days without rainfall) over Argentina. We found significant trends in several regions of the country that reflects the increments in precipitation amounts. To analyze the interdecadal variability of dry days, we apply the wavelets analysis to the longest time series available, some of them from the beginning of the 20th century. This analysis identifies significant nonstationary periodicities between 8 and 16 years, mainly in the stations of the eastern region.
2. International Conference on Drought Management, 2010/03/04-06, Istanbul (Turkey)